Cambio de virulencia en poblaciones de Mycosphaerella Graminicola Fuck Schroether sobre trigo - Cordo, C.A.=700 1 Perello, A.E.; Arriaga, H.O.
(Es, En)
ilus., 20 ref.
Keywords: VARIEDADES; TRIGO; MYCOSPHAERELLA GRAMINICOLA; SEPTORIA; VARIACION GENETICA; PODER PATOGENO; ESPAÑA; SEPTORIA TRITICI